Current rainfed maize raices in the State of Zacatecas, Mexico - Reveles-Torres, Luis Roberto; Luna-Flores, Maximino; Mejía-Gurrola, Alfonso; Hernández-Martínez, José; García Hernández, Serafín (Revista Mexicana de Ciencias Agrícolas, 2018)
Knowledge of the current genetic diversity of rainfed native maize varieties is quite important for phenotypic characterization, conservation and breeding. In 2008, a collection of such varieties was made in the State of Zacatecas, with the main objective to evaluate their diversity. The collection was made in 36 municipalities (state 58) with the largest rainfed maize and covered the different ecological regions. Ear cob characteristics and grain were measured, and ecological data collection sites were taken. 166 samples were obtained; 97 were identified with one race and 69 with two; a total of eight races were identified (three less than decades ago). Like several years ago, Cónico Norteño race had the largest presence with 51.2%; followed by Ratón and Celaya breeds with 14.7% and 14%, respectively. The Cónico Norteño race was present in all regions, but specially in low rainfall areas (260-375 mm during the growing season), the rainy season is short (65-77 days) and the elevation varies between 1 900 and 2 350 m. Celaya and Ratón races also showed a wide dispersion. Over all, the collections of higher rainfall sites had higher number of kernels per row, ear diameter and cob, grain width and weight than the collections of sites with lower rainfall. Multivariate analysis applied to the measured variables generated seven groups of collections, observing a high influence of ecological characteristics in separating the groups.
Keywords: Zea mays L.; ecological traits; genetic diversity; Zacatecas